2016
DOI: 10.3390/ijms17111782
|View full text |Cite
|
Sign up to set email alerts
|

Non-SMC Element 2 (NSMCE2) of the SMC5/6 Complex Helps to Resolve Topological Stress

Abstract: The structural maintenance of chromosomes (SMC) protein complexes shape and regulate the structure and dynamics of chromatin, thereby controlling many chromosome-based processes such as cell cycle progression, differentiation, gene transcription and DNA repair. The SMC5/6 complex is previously described to promote DNA double-strand breaks (DSBs) repair by sister chromatid recombination, and found to be essential for resolving recombination intermediates during meiotic recombination. Moreover, in budding yeast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 66 publications
3
26
0
Order By: Relevance
“…Previous reports have shown that mutation of SMC5/6 components causes sensitivity to etoposide, and SMC5/6 colocalizes and interacts with topoisomerase IIα (Gómez et al , 2013; Verver et al , 2016b). To determine whether the Smc5 mutant germ cells were also susceptible to etoposide, adult Smc5 flox/del , Stra8-Cre cKO and control mice were injected with etoposide and assessed for defects 3, 5, and 8 d postinjection (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that mutation of SMC5/6 components causes sensitivity to etoposide, and SMC5/6 colocalizes and interacts with topoisomerase IIα (Gómez et al , 2013; Verver et al , 2016b). To determine whether the Smc5 mutant germ cells were also susceptible to etoposide, adult Smc5 flox/del , Stra8-Cre cKO and control mice were injected with etoposide and assessed for defects 3, 5, and 8 d postinjection (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…Results of small interfering RNA (siRNA)-mediated knockdown and mutation studies using human cell lines reveal that depletion of the SMC5/6 complex leads to increased genome instability when exposed to exogenous DNA damage, including irradiation and etoposide exposures (Wu et al , 2012; Payne et al , 2014; Verver et al , 2016b). Therefore, we assessed whether Smc5 cKO prophase spermatocytes had elevated abnormalities when exposed to gamma irradiation and etoposide.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast SMC5/6 was observed to accumulate at sister chromatid intertwine sites, and topoisomerase II was needed for the resolution of those links [ 109 , 110 ]. Similarly, human topoisomerase II was shown to physically interact with SMC5/6 subunits, in order to resolve topological entanglements during replication [ 111 ]. Although the function of this complex is mostly outside of mitosis, its impact on chromosome organization also influences mitotic chromosome morphology.…”
Section: Regulation Of Topoisomerase II Activity: Guidance By the mentioning
confidence: 99%
“…However, we could envisage a possible prognostic implication given that Group A comprised three out the five cases with complex karyotype and TP53 mutation/17p13 loss, which are notoriously associated with a poorer outcome in AML [ 3 ]. Interestingly, NSMCE2 , which was overexpressed in Group A cases, is required for DNA double-strand break repair and genomic integrity maintenance [ 41 , 42 ]. Its depletion was shown to sensitize HeLa cells to DNA damage-induced apoptosis [ 43 ] suggesting that, alternatively, its overexpression could make tumor cells more resistant to the DNA damage induced by their wide genomic rearrangements.…”
Section: Discussionmentioning
confidence: 99%